Pressure drop characteristics of R134a during flow boiling in a single rectangular micro-channel - Keepaiboon, Chanyoot; Thiangtham, Phubate; Mahian, Omid; Dalkilic, Ahmet Selim; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The pressure-drop characteristics during flow boiling in a single rectangular micro-channel with hydraulic diameter of 0.68 mm are presented. In the present study, pressure drop was studied at heat flux range of 7.63-49.46 kW/m(2), mass flux range of 600-1400 kg/m(2) s, and saturation temperature of 23, 27 and 31 degrees C. Experimental results indicated that the total pressure was dominated by frictional pressure drop. The increase of mass flux also increased the frictional pressure gradient, whereas the increase of saturation temperature reduced the frictional pressure gradient. In addition, heat flux also had an insignificant effect on the frictional the pressure gradient. A new correlation was also proposed for effective design of micro-channel heat exchanger. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Pressure drop; Micro-channel; R134a; Flow boiling; HORIZONTAL TUBES; REFRIGERANTS; PREDICTION; CO2; Thermodynamics; Mechanics